Determinants of Student Consumptive Behavior in E Commerce Context: Faktor-faktor yang Mempengaruhi Perilaku Konsumtif Mahasiswa dalam Konteks E-Commerce - Nur Azizah; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Rapid growth of digital commerce has reshaped consumption patterns among university students. Specific Background: Increased access to online shopping platforms is associated with changes in student spending behavior. Knowledge Gap: Empirical evidence examining multiple behavioral and financial factors simultaneously in student consumptive behavior remains limited. Aims: This study analyzes factors related to consumptive behavior among university students using a quantitative approach. Results: The findings indicate that selected financial and lifestyle-related variables are statistically associated with student consumptive behavior. Novelty: The study integrates several behavioral and financial variables within a single empirical model focused on student consumers. Implications: The results provide insights for academic studies and educational institutions in understanding student consumption patterns. Keywords: Consumptive Behavior, E Commerce, Financial Literacy, Lifestyle, University Students Key Findings Highlights: Student spending patterns show strong alignment with digital purchasing habits. Behavioral factors demonstrate measurable associations with consumption tendencies. Financial understanding remains a relevant aspect of student purchasing behavior.